POISSON REGRESSION MODELING GENERALIZED IN MATERNAL MORTALITY CASES IN ACEH TAMIANG REGENCY - Sari, Riska Novita; Nabilla, Ulya; Sari, Riezky Purnama (PATTIMURA UNIVERSITY, 2023)
Maternal Mortality Rate (MMR) is the number of maternal deaths due to the process of pregnancy, childbirth, and postpartum which is used as an indicator of women's health degrees. The number of maternal deaths in Aceh Tamiang Regency in 2021 is a discrete random variable distributed by Poisson. The purpose of this study is to find out what poisson regression model is generalized in the case of MMR in Aceh Tamiang Regency in 2021 and what factors affect the AKI in Aceh Tamiang Regency in 2021. The research data was obtained from the Aceh Tamiang District Health Office. This type of research is quantitative by using the Generalized Poisson Regression method. The data used are maternal mortality rates and data on factors affecting MMR in Aceh Tamiang Regency in 2021. Influencing factors are the percentage of visits by pregnant women in K1 , percentage of visits by pregnant women K4 , percentage of maternity assistance by health workers , TT immunization of pregnant women , pregnant women who get Fe tablets , and puerperal ministry . Based on the results of research, the factors that affect the maternal mortality rate in Aceh Tamiang Regency in 2021 are TT immunizations for pregnant women (X4) with a p-value of 0.009 which states that for every additional TT immunization of pregnant women by 1%, the average maternal mortality rate also decreases by . The form of the generalized poisson regression model obtained is .